Evidence for direct involvement of T7 RNA polymerase bacteriophage DNA replication. - Hinkle, D C (1980)
Experiments in a number of different systems have suggested that the initiation of DNA replication is often dependent upon transcription at the origin of replication. During infection with bacteriophage T7, the T7 genome is transcribed first by the bacterial RNA polymerase and then by a phage-coded enzyme, the product of gene 1. The bacterial enzyme does not appear to be directly involved in the initiation of replication as phage DNA synthesis is not inhibited by rifampin. For testing whether the T7 RNA polymerase plays a role in replication, a T7 gene 1 temperature-sensitive mutant was used, and the RNA polymerase was inactivated at intervals after infection by rapidly raising the temperature of the culture. The experiments indicated that the inactivation of the T7 RNA polymerase caused the cessation of phage DNA synthesis, even at later times during infection when the inhibition of protein synthesis with chloramphenicol had no effect on DNA replication. This suggests that in addition to its role in gene expression, the T7 RNA polymerase plays a direct role in T7 DNA replication.